Remodeling the Tumor Microenvironment with Emerging Nanotherapeutics. (January 2018) - Chen, Qin; Liu, Guangxuan; Liu, Shuo; Su, Hongyan; Wang, Yue; Li, Jingyu; Luo, Cong
Abstract : The tumor microenvironment (TME) has profound impacts on cancer progression and remodeling of the TME has emerged as a strategy to facilitate cancer therapy. Recently, great progress in TME modulation has been made, especially with the rapid developments in nanomedicine. In this review we outline the latest advances in remodeling of the TME based on nanotherapeutics. First, novel strategies developed to modulate the tumor extracellular matrix (ECM) are discussed, including disruption, mimicking, and intervening in tumor ECM fabrication. Then, emerging tumor-associated fibroblast (TAF)-based nanotherapeutics are reviewed, including disruption and targeting of TAFs. Furthermore, recent developments in tumor vessel disruption and normalization are discussed. Finally, emerging approaches in response to tumor hypoxia are presented, with special emphasis on delivering oxygen, generating oxygen, and targeting tumor hypoxia. Trends: The tumor microenvironment (TME) has been recognized as a double-edged sword, creating both challenges and opportunities for cancer therapy, especially of solid tumors. The tumor extracellular matrix (ECM) plays key roles in preventing tumor metastasis but may pose a large barrier, hindering the deep penetration and perfusion of nanoparticulate drug delivery systems (nano-DDSs) in solid tumors. Tumor-associated fibroblasts (TAFs) not only contribute to the off-target disposition of nano-DDSs in stroma vessel-type tumors but also induce TAF-associated drug resistance. Tumor vessel modulation could facilitate deep penetration and perfusion of nano-DDSs and relieve tumor hypoxia. In response to hypoxia, emerging strategies are being developed to deliver oxygen, generate oxygen, or target tumor hypoxia.